Detection of Antibodies Against Tick-Borne Encephalitis Virus and Other Flaviviruses in a Zoological Collection in Slovenia - Kvapil, Pavel; Račnik, Joško; Kastelic, Marjan; Pittermannová, Pavlína; Avšič-Zupanc, Tatjana; Bártová, Eva; Sedlák, Kamil (Frontiers in Veterinary Science, 2021)
Monitoring infectious diseases is one of the most important pillars of preventative veterinary medicine in zoological collections. The zoo environment offers a great variety of different animal species living in proximity and in contact with small wild animals and vectors (e.g., ticks and mosquitos). In this context, tick-borne encephalitis virus (TBEV), Usutu virus (USUV), and West Nile virus (WNV) causing vector-borne diseases are emerging pathogens that raise concern. The aim of the study was to detect antibodies to selected flaviviruses in various animal species in the Ljubljana Zoo, Slovenia. In total, 874 sera from 96 animal species were tested for antibodies to TBEV by enzyme-linked immunosorbent assays (ELISA); positive samples were confirmed by a virus neutralization test (VNT) using TBEV, WNV, and UV antigens. Antibodies to TBEV were detected by ELISA in 3.9% (34/874) of zoo animals, with 4% (30/753) in mammals and 5% (4/86) in birds; the sera of reptiles (n = 34) and amphibians (n = 1) were negative. Antibodies to TBEV were confirmed by VNT in 11 mammals; one bird was positive for both WNV and USUV. The mixture of exotic animal species and their contact with wild animals and vectors such as ticks and mosquitos suggest that screening of infectious diseases in zoo animals might provide good insight into the epizootological situation of the area. This is the first survey of TBEV, WNV, and USUV in a zoological collection in Slovenia.